The informal economy: A neglected area in Islamic economics - Abdul Maleka, Nazurah; Mohd Arshad, Mohd Nahar (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
The informal economy has been neglected by Islamic economists. The neglect means the Islamic economic system being rebuilt is confined only to state and market domains. That existing paradigm is myopic. To understand and solve the real-world economic problems, we need to recalibrate and also focus on the informal economy. The purpose of this study, therefore, is to review the conception of the informal economy. With a better understanding of the concept, we hope that rebuilding of Islamic economics can become more holistic in approach. The informal economy is unique according to countries. The economic, political and cultural aspects have a strong influence on the dimensions of the informal economy. Based on the extant literature we also have identified the determinants of informal employment. The evaluation of the factors identified in this study reveals that government policies and efficiency, poverty issues, gender inequality, education and religiosity are the determinants of the informal sector employment. We then call for future research in Islamic economics to be geared toward understanding and addressing issues in the informal economy.